EFEKTIVITAS PENGAWASAN PERATURAN DAERAH NOMOR 4 TAHUN 2003 TENTANG PENYELENGGARAAN PONDOKAN OLEH KECAMATAN PASCA PELIMPAHAN KEWENANGAN DI KOTA YOGYAKARTA - , JUNAIDI ANDILI, S.I.P ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Rule number 4 of 2003 area on the administration of hostels one goal is to maintain peace and order in society. Along with the development of growth pondokan violations concerning the implementation of regulations pondokan often the case, this situation requires more oversight by the city of Yogyakarta. Supervision is carried out in the course of implementation pondokan experience changes in control measures. Following the delegation of authority to the district administration pondokan mayor in accordance with regulation number 14 of 2009 concerning the delegation of partial authority to the sub-district mayor to carry out the affairs of local government, requires that district in addition to issuing an operating license pondokan (SIPP) also monitor and curb the course of lodgment implementation in the city of Yogyakarta. This study aims to determine how the effectiveness of regulatory oversight area number 4 of 2003 on the administration of lodgment by the district after the delegation of authority to the township in organizing lodge. This study used descriptive research method with qualitative approach, while data collection is done by observation and in-depth interviews. Based on the theoretical framework of this study using the theory of policy effectiveness, delegation of authority, supervision, coordination and guidance and control. The results of this study indicate that there are different forms of supervision between each district, which can be differentiated into the two common forms of surveillance are: (1) form of supervision order following the department program coordinator for the city as involving districts, urban villages, RT / RW performed routinely 6 months, (2) forms of surveillance conducted by the district as a coordinator in accordance with its program of conducting routine surveillance every month involving relevant agencies such as the office of the city public order, police, koramil, village and RT / RW. Differences were also seen in the district coordination performed in the supervision, involving the relevant agencies at the district level, causing a lack of uniformity. In terms of guidance and control up to the close of business lodgment becomes less effective because it takes the recommendations of the team's integrated controller in accordance with local regulations number 4 of 2003 on the administration of huts. This certainly affects the effectiveness of supervision that should be implemented by the district that has authority in organizing hostels in the city of Yogyakarta. Advice you can give is in accordance with the district authority, should have periodic monitoring of a fixed schedule, uniform coordination between district-level institution and can do the construction and ordering directly by the district without waiting for recommendations from the team a place to stay level integrated monitoring of Yogyakarta.